Star formation and the evolution of massive galaxies across cosmic time - Ownsworth, Jamie Richard (2014)
This thesis investigates the evolution of massive galaxies throughout the last 11 billion years using measured stellar masses and star formation rates. Firstly, we present a study of the resolved star-forming properties of a sample of distant massive (M > 10{11} M) galaxies in the GOODS NICMOS Survey (GNS) within the redshift range 1.5 < z < 3 in order to measure the spatial location of ongoing star formation (SF). We find that the SFRs present in different regions of a galaxy reflect the already existent stellar mass density, i.e. high density regions have higher SFRs than lower density regions, on average. We find that these massive galaxies fall into three broad classifications of SF distributions. These different SF distributions increase the effective radii to z=0, by ~16 plus-minus 5 % , with little change in the Sersic index (n), with an average delta n = -0.9 plus-minus 0.9, after evolution. These results are not in agreement with the observed change in the effective radius and n between z ~2.5 and z ~0. We conclude that SF and stellar migration alone cannot account for the observed change in structural parameters for this galaxy population, implying that other mechanisms must additionally be at work to produce the evolution, such as merging. In Chapter 2, we present a study of the stellar mass growth of the progenitors of local massive galaxies at number densities of n < or = 1x10{-4} Mpc{-3} in the redshift range 0.3<z<3.0. We select the progenitors of massive galaxies using two number density selection techniques: a constant number density selection, and one which is adjusted to account for major mergers. We find that the direct progenitors of massive galaxies grow by a factor of four in total stellar mass over this redshift range. On average the stellar mass added via the processes of star formation, major, and minor mergers account for 23 plus-minus 8 %, 17 plus-minus 15 % and 35 plus-minus 14 %, respectively, of the total galaxy stellar mass at z=0.3. Therefore, 52 plus-minus 20% of the total stellar mass in massive galaxies at z=0.3 is created externally to local massive galaxies. We examine the dominance of these processes across this redshift range and find that at z>1.5 SF is the dominant form of stellar mass growth, while at z<1.5 mergers become the dominant form with minor mergers the dominant form of growth at z<1.0. We also explore the implication of these results on other galaxy formation processes such as the cold gas accretion rate of the progenitors of most massive galaxies over the same redshift range. We find that the gas accretion rate decreases with redshift with an average gas accretion rate of ~65 M yr{-1} over the redshift range of 1.5<z<3.0. Finally, we investigate the evolution of the properties of local massive galaxies over the redshift range 0.3<z<3.0. We again select the progenitors of local massive galaxies using a constant number density selection. We find that the average progenitor galaxy appears passive in $UVJ$ colours since at least z=3.0. We examine the UVJ colours and find that the average progenitor of a local massive galaxy has not lived on the blue cloud since z=3.0. The passive fraction of the progenitor population has increased from 56 plus-minus 7% at z=3.0 to 94 plus-minus 8% at z=0.3. This result implies that the majority of the progenitors of local massive galaxies have stopped actively star forming by z=3.0. Examining the structural properties of the progenitor galaxies we show that the size evolution of a galaxy sample selected this way is on average lower than the findings of other investigations into the size evolution of massive galaxies which have found that they must grow in size by a factor of 2-4 from redshift 3.0 to the present day. The average n of the progenitor population evolves significantly over the redshift range studied, with the population being dominated by low n objects (n<2.5) at z>1.7 and transitioning to high n objects at z<1.7. Splitting the high and low $n$ objects into SFing and passive samples. We find that 41 plus-minus 4 % of the sample at z>2.5 are passive low n systems, possibly implying that local massive galaxies were passive disk-like systems at early cosmic times.